A simple benzimidazole quinoline-conjugate fluorescent chemosensor for highly selective detection of Ag+. Issue 27 (7th July 2016) - Chen, Changjun; Liu, Haiyang; Zhang, Bin; Wang, Yanwei; Cai, Kai; Tan, Ying; Gao, Chunmei; Liu, Hongxia; Tan, Chunyan; Jiang, Yuyang
Abstract: A novel and simple fluorescent chemosensor (L ), N -((1H-benzo[d]imidazol-2-yl)methyl)quinoline-2-carboxamide, based on quinoline benzimidazole scaffold was synthesized successfully, which had a 'turn-on' effect for Ag + detection in methanol/Tris buffer(1:1, v/v, pH=7.35) and exhibited a strong fluorescence emission at 357 nm ( λ ex =300 nm). The chemosensor had high sensitivity and selectivity for Ag + even in the presence of other metal ions with the detection limit of 4.4×10 −7 M, which reached the standard of World Health Organization (WHO) for drinking water (5.0×10 −7 M). The mechanism of the interaction between the sensor and Ag + was investigated in detail through NMR and MALDI Mass spectra analysis. Graphical abstract: A quinoline benzimidazole scaffold based fluorescence probe was synthesized successfully, which had 'turn on' effect for detecting Ag + with high selectivity and good sensitivity.